ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MEP-UGM DALAM MEMILIH LOKASI KOS TAHUN 2011 - CHANDRA, ADY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Along with the development education in the city of Yogyakarta affecting on the development of boardinghouse business. Right now boardinghouse is not only focused on the location close to campus, but now has grown up in the suburbs are even located far to the campuses, so the impact on business competition among the owner of boardinghouse. Issues that happened is it can be formulated problems that occur is still a lack of information / knowledge to determine the location of where you should build a boarding, whether near or far from the college campus. The purpose of this research was to analyze faktors that affect student interest MEP-UGM in choosing a boardinghouse location and to analyze the most dominant variables that affect the MEP-UGM student interest in choosing a boardinghouse location. Data used in this research is the primary data obtained from student questionaires and secondary data from MEP-UGM student data obtained from generation of the 42-45 academic MEP-UGM campus. Analysis tools be used in this research is logit regression using the EVIEWS program to know the attributes or variables that are considered most important or most influential of the MEP-UGM student interest in choosing location of boarding house. Results of research by using the logit regression analysis found that of four independent variables that is rents, environmental, facilities and accessibility, was only one variable that does not affect is a variable the rental price. The main attributes that most influence on student interest in choosing a boardinghouse locations are environmental factors. The second attribute the most influential is accessibility factor and the third factor is facility factors.